1990
DOI: 10.1007/bf02244604
|View full text |Cite
|
Sign up to set email alerts
|

Effect on radiolabelled-monoamine uptake in vitro of plasma taken from healthy volunteers administered the antidepressant sibutramine HCl

Abstract: Sibutramine HCl, a monoamine reuptake inhibitor type of antidepressant, was administered to healthy male volunteers as either a single dose (12.5 or 50 mg) or repeated treatment (5-20 mg once daily or 15 mg twice daily). Plasma, obtained at regular intervals during and after sibutramine HCl or placebo treatment, was assayed in vitro for its ability to inhibit the uptake of [3H]-noradrenaline (NA) by rat cortical synaptosomes, [3H]-5-hydroxytryptamine (5HT) by human platelets and [14C]-dopamine (DA) by rat stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 20 publications
4
23
2
Order By: Relevance
“…The limited pre-existing literature in animals and humans suggested that central SERT occupancy associated with 15 mg of sibutramine daily may be very low or even indistinguishable from placebo (Luscombe et al, 1990;Thomas et al, 2009). We have demonstrated that it can be measured accurately by 11 C-DASB PET and, although of modest magnitude (mean 30%), is clearly not negligible in humans.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The limited pre-existing literature in animals and humans suggested that central SERT occupancy associated with 15 mg of sibutramine daily may be very low or even indistinguishable from placebo (Luscombe et al, 1990;Thomas et al, 2009). We have demonstrated that it can be measured accurately by 11 C-DASB PET and, although of modest magnitude (mean 30%), is clearly not negligible in humans.…”
Section: Discussionsupporting
confidence: 40%
“…This lack of efficacy is not clearly related to the dose of sibutramine received (McNeely and Goa, 1998), and possible mechanisms underlying non-response are poorly understood. In a study of healthy male volunteers administered sibutramine 5, 10 or 20 mg once daily for 14 days, the doses below 20 mg did not reliably inhibit 3 H-5-HT uptake in an in vitro human platelet SERT preparation (Luscombe et al, 1990). Even the 20 mg dose could not be distinguished from placebo, although it showed 20-30% inhibition.…”
Section: Introductioncontrasting
confidence: 39%
“…Currently available pharmacological treatment for obesity is based on a range of drugs with different mechanisms of action, including drugs that affect energy intake and energy expenditure and those preventing dietary fat absorption (for review, see Clapham et al, 2001). Sibutramine hydrochloride (BTS 54 524;cyclobutyl]-3-methylbutyl}-N, N-dimethylamine HCl monohydrate) is a member of a novel class of drugs that inhibits the reuptake of both serotonin (5-HT) and norepinephrine (NE) (Luscombe et al, 1989(Luscombe et al, , 1990, although details of the interaction between the drug and/or its metabolites and the NE and 5-HT transporter proteins (for review, see Goldberg et al, 2003) are not available. Sibutramine is currently indicated for the management of obesity (for reviews, see Stock, 1997;Luque and Rey, 2002).…”
mentioning
confidence: 42%
“…Sibutramine hydrochloride is a novel serotonin and noradrenaline reuptake inhibitor 6 (SNRI) with weight-reducing properties. In both animals and humans, it potently inhibits the reuptake of serotonin (5-HT) and noradrenaline, 6,7 but not dopamine. 7,8 Sibutramine represents a new class of agent for the treatment of obesity that differs from drugs such as fen¯uramine and d-fen¯uramine, which exclusively activate 5-HT systems, and from drugs such as d-amphetamine, mazindol and the b 3 -adrenoreceptor agonists, which exclusively activate catecholamine systems.…”
Section: Introductionmentioning
confidence: 48%